Egg intervention effect on linear growth no longer present after two years. Issue 2 (17th December 2019) - Iannotti, Lora L.; Chapnick, Melissa; Nicholas, Jennifer; Gallegos‐Riofrio, Carlos Andres; Moreno, Patricia; Douglas, Katherine; Habif, David; Cui, Yuhan; Stewart, Christine; Lutter, Chessa K.; Waters, William F.
Abstract: The Lulun Project, a randomized controlled trial conducted in 2015, found that one egg per day for 6 months during early complementary feeding reduced stunting by 47% and increased linear growth by 0.63 length‐for‐age Z (LAZ). This follow‐up cohort study (Lulun Project II) aimed to test whether the growth effect remained in the egg intervention group compared with the control group after approximately 2 years. Mothers or caregivers from the Lulun Project were recontacted and recruited for this study. Enumerators collected data on socio‐economic and demographic factors, 24‐hr frequency of dietary intakes, morbidities, and anthropometric measures of height, weight, and head circumference using World Health Organization protocols. Statistical analyses followed the same analytical plan as Lulun Project, applying generalized linear models and regression modelling to test group differences in height‐for‐age z (HAZ) from LAZ at Lulun Project endline, and structural equation modelling for mediation. One hundred thirty‐five mother–child dyads were included in Lulun II, with 11% losses to follow‐up from endline Lulun Project. Growth faltering across all children was evident with HAZ −2.07 ± 0.91 and a stunting prevelance of 50%. Regression modelling showed no difference between egg and control groups for the HAZ outcome and other anthropometric outcomes, and significant declines in HAZ from endline Lulun Project in the egg intervention are compared with control groups. Current dietary egg intake, however, was associated with reduced growth faltering in HAZ from Lulun Project endline to Lulun Project II, independent of group assignment and through mediation, explaining 8.8% of the total effect. Findings suggest the need for a longer intervention period and ongoing nutrition support to young children during early childhood.